Asymmetric Cournot Duopoly: A Game Complete Analysis - Carfi, David; Perrone, Emanuele (Journal of Reviews on Global Economics, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">In this paper, we apply the Complete Analysis of Differentiable Games (introduced by D. Carfì in Topics in Game Theory (2012), <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">Carfì ICT 2009<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">, <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">Carfì AAPP 2009<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">, Carfì <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">GO 2009<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">; already employed by himself and others in <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">Carfì TPREF 2011<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">, <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">Carfì AAPP 2010<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">, <span style="font-size: 10.0pt; mso-bidi-font-size: 8.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">Carfì ISGC 2009<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Baskerville; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">) and some new algorithms, using the software wxMaxima 11.04.0, in order to reach a total scenario knowledge (that is the total knowledge of the payoff space of the interaction) of the classic Cournot Duopoly (1838), viewed as a complex interaction between two competitive subjects, in a particularly interesting asymmetric case. Moreover, in this work we propose a theoretical justification, for a general kind of asymmetric duopolistic interactions (which often appear in the real economic world), by considering and proposing a Cobb-Douglas perturbation of the classic linear model of production costs.